2021
DOI: 10.1039/d1fo00290b
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of Lactobacillus-fermented black barley on high fat diet-induced fatty liver in rats

Abstract: Long term high-fat diet (HF) can cause metabolic disorders, which might induce fatty liver. Fermented whole cereal food exhibit healthy potential due to their unique phytochemical composition and probiotics. In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
3
13
0
Order By: Relevance
“…Our results show that the functional components (polyphenol, flavone) were enhanced by KBF. Previous studies have also proved fermented grains could enrich certain functional components after fermentation, such as barley or black barley with probiotics and kidney beans fermented with Pleurotus ostreatus [ 9 , 33 ]. This may be because probiotic fermentation promotes the release of polyphenols and flavonoids in raw kidney beans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results show that the functional components (polyphenol, flavone) were enhanced by KBF. Previous studies have also proved fermented grains could enrich certain functional components after fermentation, such as barley or black barley with probiotics and kidney beans fermented with Pleurotus ostreatus [ 9 , 33 ]. This may be because probiotic fermentation promotes the release of polyphenols and flavonoids in raw kidney beans.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have confirmed that the proportion of polyphenols that are enriched after fermentation intake should be increased in a reasonable diet structure to prevent hyperlipidemia, and the functional components play a potential hypolipidemia-lowering effect through different regulatory mechanisms [ 8 , 9 ]. For example, flavonoids in oats inhibit fat production and promote its decomposition [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes result from the microbial metabolic activities that mainly break down carbohydrate fractions into several end products, such as acids. The presence of multiple end products and the release of several phytochemicals deliver various health-promoting properties, such as the prevention of cardiovascular disease [ 11 ], hypertension [ 12 , 13 , 14 , 15 ], obesity [ 16 , 17 ], and osteoporosis [ 18 ]. In addition, a variety of fermented foods have shown antidiabetic effects both in vitro and in vivo [ 6 ] using a wide range of different microorganisms as starter cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Nucleotides are important low-molecular-weight compounds that participate in the regulation and metabolism of various substances as free nucleotides or their derivatives ( Wang et al, 2021a ; Guan et al, 2021 ; Lu et al, 2021 ; Santos Ferreira et al, 2021 ). Free mononucleotides are the main high-energy compounds involved in energy metabolism, important messengers in cellular signal transduction, and metabolic regulators of various nutrients in the body ( Wang et al, 2021a ; Guan et al, 2021 ; Lu et al, 2021 ; Santos Ferreira et al, 2021 ). Addition of exogenous nucleotides can nourish lymphocytes, promote their differentiation, and inhibit DNA damage.…”
Section: Introductionmentioning
confidence: 99%